2011
DOI: 10.1007/s00128-011-0197-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Aluminum by Lemna gibba L. from Secondary Treated Municipal Wastewater Effluents

Abstract: In this study, Lemna gibba as a sample aquatic plant was used to remove Al from a municipal secondary waste water effluence. Lemna gibba was acclimatized to the effluent in situ. The concentration of Al in the plant samples was examined for 7 days. Lemna gibba accumulated 500 μg Al g⁻¹ on the first day and reached saturation level with an increase of 100 μg g⁻¹ on the second day. The results indicated that Lemna gibba can be used as an effective aquatic plant at low costs for the treatment of municipal seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…L. minor met the basic characteristics of metal hyperaccumulation and was found to be a hyperaccumulator of both Ni and Cr in all experimental concentrations. Obek () determined L. gibba L.'s heavy metal accumulating capability in secondary treatment effluence and found it to have high ability to remove Cr in secondary treatment effluence as well: 300% on the first day, 360% on the second day and 500% on the fifth day of experimental period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…L. minor met the basic characteristics of metal hyperaccumulation and was found to be a hyperaccumulator of both Ni and Cr in all experimental concentrations. Obek () determined L. gibba L.'s heavy metal accumulating capability in secondary treatment effluence and found it to have high ability to remove Cr in secondary treatment effluence as well: 300% on the first day, 360% on the second day and 500% on the fifth day of experimental period.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, L. minor might be useful in the treatment of water contaminated with Ni and Cr, individually. Obek () determined Ni accumulation using L. gibba L. in secondary treatment effluents, but observed no significant changes in Ni accumulation levels during the seven day experimental period. According to results by Appenroth et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic phytoremediation with floating aquatic plants for nutrient removal has a large potential, especially in tropical and subtropical regions of the world (Olguín et al, 2008). Among these species may be cited: Azolla caroliniana Willd, Salvinia minima Baker and Lemna gibba Linnaeus (Mkandawire & Dudel, 2005;Olguín et al, 2008;Hayes, 2010;Obek & Sasmaz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased incidences of cancer in some villages of this basin might result from water pollution (Yin 2005). Previous investigations have shown that the metals in the Shaying River pose a potential risk on ecosystem safety and public health, mainly because many of them, e.g., lead, cadmium and chromium, bio-accumulate in aquatic food chains (Obek 2009;Walkuska et al 2010). Even at low aqueous concentrations, the metals can damage the nervous system (Johnson and Atchison 2009) and disrupt the immune system (Mishra 2009).…”
Section: Introductionmentioning
confidence: 99%